Faith Missions and Protestant churches in Costa Rica: origin, organization and institutional platform (1890-2019) - Meza Li, Jennifer (2025)
Religious competition began in Costa Rica at the end of the 19th century with American Protestant faith missions and churches, primarily those of the historical and evangelical movement, and, beginning in the 1920s, those of the Pentecostal movement. These churches have established an operational, organizational, and institutional platform, such as theological training institutions, associations, media outlets, social projects, and political parties, which have allowed them to grow and achieve greater influence.